ANALYSIS OF OCCUPATIONAL ACCIDENT RISK FACTORS AMONG HIGH-RISE BUILDING CONSTRUCTION WORKERS IN SOUTH LAMPUNG REGENCY - Ahmad Fauzi; Roma Yuliana; Putri Rahmadani; Prasita Ayu Widyaningtyas; Artha Budi Susila Duarsa; ST. Austa Nursa; Ikrimah Nafilata; Nazara Jinggan Aziza (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Construction is a high-risk sector because workers are exposed to physical, mechanical, electrical, ergonomic, and dynamic workplace hazards. This study aimed to analyze the association between worker characteristics (age, work experience, education level, and work division), occupational safety and health (OSH) knowledge, personal protective equipment (PPE) use, and occupational accidents among high-rise building construction workers at PT. Razar Bumi Perkasa, South Lampung Regency. The study was motivated by the high occupational accident rate in Indonesia in 2024 and the absence of division-specific accident risk data in this company. The study was conducted in April 2026 at the high-rise building construction site of PT. Razar Bumi Perkasa in South Lampung Regency. This study utilized a quantitative-analytical research design with a cross-sectional method. The population consisted of 179 workers, and 50 respondents were selected using simple random sampling based on Slovin's formula (e=10%). Data were collected using a structured questionnaire that had been tested for validity and reliability. The OSH knowledge variable was measured with 32 items (cut-off point: median = 122), PPE use with 16 items (cut-off point: median = 65), and occupational accident risk with 19 items (cut-off point: median = 39). Data were analyzed using univariate and bivariate analyses with the Chi-Square test (α = 0.05). Most respondents were categorized as having a high risk of occupational accidents (52.0%). Work division was significantly associated with occupational accidents (p=0.019), with the highest high-risk proportions observed in the MEP (80.0%) and civil (61.3%) divisions. Age (p=0.534), education (p=0.384), work experience (p=0.623), OSH knowledge (p=0.089), and PPE use (p=0.963) were not significantly associated with occupational accidents. Occupational accident risk was more strongly related to job characteristics and division-specific hazard exposure than individual factors. Accident prevention should prioritize division-based risk control, field supervision, housekeeping improvement, and OSH culture strengthening